2021
DOI: 10.1590/1980-54702021v27e0161
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Indicators of the Use of Lesson Study as a Teaching Practice Capable of Enabling an Inclusive Perspective in Higher Education

Abstract: This study approached the Lesson Study strategy as a support for planning academic activities of teachers who intend to adopt or contribute to the adoption of an inclusive perspective in Higher Education. The general objective of this study was to describe preliminary indicators of the use of the Lesson Study as a teaching practice capable of enabling an inclusive perspective, in the context of Higher Education. Specifically, we aim to: a) identify strategies by student with and without markers (social, lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
1
0
3
Order By: Relevance
“…Past studies show the different kinds of strategies such as sharing error sheets, using color codes to identify errors and having the students correct them as an appropriate strategy to avoid the usage of red markers (Azeez, 2021;De Oliveira et al, 2021;Núñez-Peña & Bono, 2022). Furthermore, Diab (2022) recommended the use of a peer corrective feedback approach to improve ESL students' writing and language skills instead of the instructor's direct feedback with red markers.…”
Section: Pedagogical Strategies In Pamentioning
confidence: 99%
“…Past studies show the different kinds of strategies such as sharing error sheets, using color codes to identify errors and having the students correct them as an appropriate strategy to avoid the usage of red markers (Azeez, 2021;De Oliveira et al, 2021;Núñez-Peña & Bono, 2022). Furthermore, Diab (2022) recommended the use of a peer corrective feedback approach to improve ESL students' writing and language skills instead of the instructor's direct feedback with red markers.…”
Section: Pedagogical Strategies In Pamentioning
confidence: 99%
“…Considering that the focus of these interviews was to obtain tips, strategies, and other aspects they found it important to improve the discussions of that class with an inclusive perspective, for the next cycle. Some of the aspects indicated by the students were highlighted in the study by Oliveira, Bracken and Nakano (2021), and those indicated by the teachers after all the analyzes of cycle 1, the focus of this paper, are shown in Figure 3, below. Oliveira, Bracken and Nakano (2021) verified that, during the observations and in the postobservation discussions, the students consistently expressed the need to articulate more clearly how the content being taught related to the expectations of the assessment processes.…”
Section: Preparation Cycles Of Lesson Studymentioning
confidence: 99%
“…Some of the aspects indicated by the students were highlighted in the study by Oliveira, Bracken and Nakano (2021), and those indicated by the teachers after all the analyzes of cycle 1, the focus of this paper, are shown in Figure 3, below. Oliveira, Bracken and Nakano (2021) verified that, during the observations and in the postobservation discussions, the students consistently expressed the need to articulate more clearly how the content being taught related to the expectations of the assessment processes. The assessment was a central point during the application of cycle 1 and the discussions arising from it.…”
Section: Preparation Cycles Of Lesson Studymentioning
confidence: 99%
“…Pontanto, o estudo de aula no ensino superior constitui um potencial contexto para promover o desenvolvimento profissional de professores universitários, contribuindo para promover mudanças no ensino (Alvine et al, 2007;Burroughs e Luebeck, 2010;Helvia Artime et al, 2015;Leavy, 2015;Oliveira et al, 2021;PNA 17(1) Richit, 2021a), favorecer aprendizados de futuros professores em componentes associadas à formação profissional, tais como Estágio Curricular Supervisionado (Neves et al, 2022), assim como melhorar o conhecimento matemático sobre tópicos específicos e sobre as bases subjacentes a docência na universidade. Nesta perspectiva, o estudo de aula desenvolvido com formadores de futuros professores, por envolver professores universitários com diferentes níveis de experiência profissional no planejamento colaborativo, na observação da prática e posterior reflexão, constitui um contexto de desenvolvimento profissional que mobiliza e desenvolve distintos aspectos do conhecimento profissional, inerentes à docência em cursos de licenciatura, assim como sobre outros aspectos intrínsecos a essa função e a sua finalidade.…”
Section: Pna 17(1)unclassified